Influence of Er substitution for La on the thermal conductivity of (La1−xErx)2Zr2O7 pyrochlores. (April 2015) - Zhang, Yonghe; Xie, Min; Zhou, Fen; Cui, Xiangzhong; Lei, Xingeng; Song, Xiwen; An, Shengli
Graphical abstract: The substitution of Er 3+ for La 3+ effectively reduces the thermal conductivity of La2 Zr2 O7 . With the increasing Er 3+ content, the thermal conductivity significantly decreases at lower temperatures. At higher temperatures, however, the thermal conductivity of the (La1− x Er x )2 Zr2 O7 becomes similar, indicating that the thermal conductivity is less sensitive to composition variation. Highlights: The substitution of Er 3+ for La 3+ reduces the thermal conductivity of La2 Zr2 O7 . The thermal conductivity reveals a nearly temperature-independent behavior. A novel phonon scattering source (rattlers) was found in this study. The rattlers are more efficient in scattering low frequency phonons. The present study also provides a novel way to reduce the thermal conductivity. Abstract: The influences of Er2 O3 doping on the structure and thermophysical properties of La2 Zr2 O7 were investigated. The (La1− x Er x )2 Zr2 O7 ceramics were synthesized by a solid state reaction method. The XRD results indicate that they all consist of the pure pyrochlore structure. The SEM results show that the microstructure of the sintered ceramics is dense and the grain boundaries are clean. The average thermal expansion coefficients of the (La1− x Er x )2 Zr2 O7 ceramics range from 9.57 × 10 −6 K −1 to 9.66 × 10 −6 K −1 . The substitution of Er 3+ for La 3+ effectively reduces the thermal conductivity of La2 Zr2 O7 . With the increasing Er 3+ content, the thermal conductivity significantly decreases at lower temperatures. At higher temperatures, however, the thermal conductivity of the (La1− x Er x )2 Zr2 O7 becomes similar, indicating that the thermal conductivity is less sensitive to composition variation. In addition, for the composition with x = 0.10, the thermal conductivity reveals a nearly temperature-independent behavior, which should be ascribed to the strong phonon scattering source (rattlers).